2019
DOI: 10.1002/bdr2.1469
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposures during pregnancy: Mechanistic effects on immunity

Abstract: In human studies, it is well established that exposures during embryonic and fetal development periods can influence immune health. Coupled with genetic predisposition, these exposures can alter lifetime chronic and infectious disease trajectory, and, ultimately, life expectancy. Fortunately, as research advances, mechanisms governing long‐term effects of prenatal exposures are coming to light and providing the opportunity for intervention and risk reduction. For instance, human association studies have provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 185 publications
(261 reference statements)
0
10
0
Order By: Relevance
“…PM 2.5 also affects the immune system, although only a handful of human studies relevant to early life exposure are published to date [ 21 , 22 ]. Herr et al [ 23 ] observed that prenatal exposure to PM 2.5 shifted lymphocyte distributions representative of the neonatal adaptive immune response in umbilical cord blood.…”
Section: Human Evidence From Epidemiologic Studiesmentioning
confidence: 99%
“…PM 2.5 also affects the immune system, although only a handful of human studies relevant to early life exposure are published to date [ 21 , 22 ]. Herr et al [ 23 ] observed that prenatal exposure to PM 2.5 shifted lymphocyte distributions representative of the neonatal adaptive immune response in umbilical cord blood.…”
Section: Human Evidence From Epidemiologic Studiesmentioning
confidence: 99%
“…Our finding that gestational exposure to air pollution is linked to global decreases in cytokine responses at birth begs the question of whether cytokine levels measured at birth have an effect on health across the course of the child’s life. Some studies have found lower levels of cord blood cytokines associated with a greater likelihood of adverse child health outcomes such as wheeze, eczema, and other allergic disorders [ 56 ], supporting the idea that decreases in cytokine responses at birth are related to later health [ 57 ]. In Project Viva, a study of 446 mother-child pairs found that lower levels of cord blood IFN-γ were associated with a higher risk of acute lower respiratory infection in the first year of life [ 58 ].…”
Section: Discussionmentioning
confidence: 97%
“…An altered intrauterine homeostasis can lead to neuro-immune and peripheral immunologic alterations, and thus can impact long-term health and result in lifelong disabilities. 36 39 Immune system reprogramming in the fetus can occur during critical immunotoxic prenatal windows during the prenatal period 40 due to exposures to inflammation or infection, and can skew immune responses, thus contributing to disease processes and mortality. 34 …”
Section: Intra-amniotic Infection (Iai)/histologic Chorioamnionitis (...mentioning
confidence: 99%